Viewing the model of the new law school building (Institutional Knowledge at Singapore Management University, 2014)
SMU President Arnoud De Meyer; Professor Yeo Tiong Min, Dean, School of Law; Attorney-General Steven Chong; Chancellor Yong Pung How; Dr Jonathan Marshall, son of David Marshall; Ms Ho Ching, CEO of Temasek Holdings; Mr Ho Kwon Ping, Chairman. Board of Trustees—being briefed by the architect about the new School of Law building.